Reinterpreting Islamic Authenticity: Hassan Hanafi's Sacred-Profane Dialectic and Its Implications for Social Transformation - Ananda, Rifki Abror; Fata, Ahmad Khoirul; Parray, Tauseef Ahmad (RaSAIL Media Group, Semarang, Indonesia, 2025)
This article explores the dialectic between the sacred and the profane in Hassan Hanafi's Islamic Leftism, focusing on its implications for Islamic authenticity and social transformation. The study addresses the issue of how religious traditions, often perceived as static, can be reinterpreted to address contemporary social challenges such as economic inequality and political oppression. Employing a textual analysis method, the research examines Hanafi's key works, including Min Al-Aqidah Ila Al-Thawrah and Al-Turath wa al-Tajdid, to analyze his critique of traditional Islamic conservatism and his emphasis on the dynamic role of sacredness in driving social change. The findings reveal that Hanafi redefines Islamic authenticity by integrating spiritual values with practical social action, challenging the overemphasis on transcendental aspects in Sufism. This study contributes to the discourse on Islamic thought by offering a new framework that bridges spirituality with societal transformation, providing insights for scholars and policymakers seeking to reconcile religious traditions with modern challenges.